The Influence Of Compensation And Work Motivation On Perception Of Performance With Gender Moderation In Fast Food Employees In Jakarta - Ayuningtyas, Ari Hartanti; Fadli, Jul Aidil (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The coffee shop business is a form of business that is quite attractive to entrepreneurs as producers and the wider community as consumers. As is currently busy in the business world, coffee shops are a form of business that is quite attractive to entrepreneurs as producers and for the wider community as consumers. In managing this coffee shop business, coffee shop owners must compete with many other coffee shops, so coffee shop owners must have two good business strategies and innovation and creativity in managing all components that support the running of this coffee shop business. This study aims to determine the effect of Salary and Work-life Balance on Employee Productivity with the mediation of Work Motivation of Coffee Shop Employees. This research was conducted on coffee shop employees who have worked for at least 3 months in Jabodetabek. The sampling method used purposive sampling with a sample size of 170 respondents. The number of statements given to respondents was 17 statement items. The results of this study indicate an insignificant effect on salary with employee productivity, a significant effect on work-life balance on employee productivity, a significant effect of salary on employee work motivation, then a significant effect of work-life balance on employee work motivation , a significant effect of employee work motivation on work-life balance and an insignificant mediating effect on employee work motivation with salary and employee productivity, the mediating effect of employee work motivation with work-life balance and employee productivity. Keywords:Employee Productivity, Employee Motivation, Work-Life Balance, Salary